Rencontres religieuses et dynamiques sociales au Burkina Faso - Degorce, Alice; Kibora, Ludovic O.; Langewiesche, Katrin (Amalion, 2019)
"Burkina Faso’s religious landscape, where traditional, Muslim and Christian religions intersect, is part of a social and historical context spread over several centuries marked by a diversity that has been studied by researchers for a long time. As the security situation deteriorates in recent years in the Sahel region, the religious question is increasingly being redefined and put at the forefront of the Burkinabe socio-political scene. This collective work offers readers a synthesis of the knowledge accumulated by researchers over the past decades on the different religions and the social dynamics associated with them to shed light on the management of the country’s religious diversity and coexistence amidst the tensions and conflicts being faced."--Vendor website